The Effect of Education Level, Health Level, and Income Inequality on Regency/City Poverty Level in West Sumatra Province 2016-2021 - Eko Pratama Putra; Mulyo Hendarto Robertus (Universitas Diponegoro, 2022)
The poverty rate in the province of West Sumatera is still high, the poverty rate can be seen in the statistics of the province of West Sumatera. This study analyzes several factors that influence the level of poverty in the province of West Sumatera. This study aims to analyze the effect of education level, health level and income inequality on poverty in districts/cities in West Sumatera Province in 2016-2021. This study uses panel data from 2016 to 2021 with a research sample of 19 cities / districts in West Sumatera Province. The analysis used in this research is the Fixed Effect Model (FEM) approach using Least Square Dummy Variable (LSDV). The panel regression model used in this study has tested classical assumptions, detected no multicollinearity, autocorrelation, heteroscedasticity, and normally distributed data, with an R-squared of 0.97. Based on the partial research that affects the level of poverty, namely the level of education and the level of health. Income inequality does not affect poverty levels. If viewed simultaneously or together, these variables can affect the level of poverty. Suggestions that can be submitted are that the government pays attention to the level of education, the level of public health. To the community to realize the importance of education and health in order to reduce the level of poverty.